Induction of SCEs and DNA fragmentation in bovine peripheral lymphocytes by in vitro exposure to tolylfluanid-based fungicide - Siviková, Katarína (Sociedade Brasileira de Genética, 2011)
The potential for genotoxic and cytotoxic effects of tolylfluanid-based fungicide (50% active agent) was evaluated using sister chromatid exchange (SCE) and proliferation indices (PI) in cultured bovine peripheral lymphocytes. For the detection of possible genetic damage, DNA fragmentation assay was also applied. Bovine lymphocytes cultured for 72 h were treated with the fungicide at the final concentrations of 1.75, 3.5, 8.75, and 17.5 μg/mL for the last 24 and 48 h of culture without S9 metabolic activation, and during the last 2 h of culture with S9 metabolic activation. In the SCE assays no evidence for genotoxic activity of the fungicide was found in treatments of 24 h without and 2 h with S9. After the 24 h exposure to tolylfluanid, a weak decrease in the PI was observed. With the prolonged exposure time (48 h), dose dependence in the increase of SCE frequencies was observed. Moreover, after 48 h exposure slight fragmentation of DNA at the concentrations of 3.5 and 8.75 μg/mL was demonstrated. SCE quantification is the most widely used approach for the assessment of genotoxic/cytogenetic effects of chemical compounds. Positive results in the assay at 48 h exposure indicated a potential of the fungicide to increase frequency of chromosomal damage (replication injuries) that is the confirmation of early effect of exposure.